2007
DOI: 10.1504/ijeb.2007.012974
|View full text |Cite
|
Sign up to set email alerts
|

Understanding one aspect of the knowledge leakage concept among SMEs: people

Abstract: To guarantee the success of a commercial organisation in the present tremendously competitive world, managers need to enhance best practices and retain in-house knowledge and experience. An organisation's competitive advantage can be lost if knowledge and/or experience is lost or 'leaked'. The research described here explores whether organisations are aware of knowledge leakage routes via people, and the positive and negative consequences that can result. The concept of knowledge leakage is not well understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…In the securing of these information-based IC components, all three aspects of information security apply: confidentiality, integrity and availability of the information (Desouza, 2006). In the first place, the organization has to retain control over the extent of IC report disclosures (Baughn et al, 1997;Mohamed et al, 2006;Laperche, 2018), in much the same way as it controls disclosure of its other information assets. This is arguably a confidentiality concern.…”
Section: Step 2: Governing Ic Securitymentioning
confidence: 99%
“…In the securing of these information-based IC components, all three aspects of information security apply: confidentiality, integrity and availability of the information (Desouza, 2006). In the first place, the organization has to retain control over the extent of IC report disclosures (Baughn et al, 1997;Mohamed et al, 2006;Laperche, 2018), in much the same way as it controls disclosure of its other information assets. This is arguably a confidentiality concern.…”
Section: Step 2: Governing Ic Securitymentioning
confidence: 99%
“…A case study was conducted on knowledge leakage by people in SMEs (Mohamed et al, 2006). They found that when employees migrate from one company to another, there is a high possibility that knowledge acquired from the former company may be leaked to another.…”
Section: Employees' Movements/ People Interactionmentioning
confidence: 99%
“…Information/Knowledge leakage triggered by organisational incentives (Zhang, 2011;Anand and Goyal, 2009;Bonte and Wiethaus 2007;Harhoff et al, 2003;Lee, 2002) Information/Knowledge leakage triggered by individual incentives (Faisal et al, 2007) Information/Knowledge leakage through outsourcing/joint-venture/sub-contracting activities (Faisal et al, 2007;Hoecht and Trott, 2006a;Hoecht and Trott, 2006b) Information/Knowledge leakage arising from employee movement/people interaction (Mohamed et al, 2006;Kovach et al, 2004) From the literature, we identified that both academics and practitioners paid little attention to information and knowledge leakage management. IKL may represent a major loss to any firm if it is not managed properly.…”
Section: Findings Reported Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Business knowledge and experience characteristically reside only in individuals' minds, and thus, the transfer of knowledge and experience explicitly to business processes is very difficult. However, Mohamed, Mynors, Grantham, Walsh, and Chan (2006) argue that when employees change positions, move to new organizations, or retire, their knowledge certainly leaves with them, causing a permanent void in an organization (Bohn, 1994). Hence, organizational knowledge base exteriorizes the business process mechanism, which influences performance by retaining relevant knowledge and experience.…”
Section: Theoretical Backgroundmentioning
confidence: 99%